2016
DOI: 10.3390/molecules21111558
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacteria and Hydrogen Sulfide: The New Old Players in Circulatory System Homeostasis

Abstract: Accumulating evidence suggests that gut bacteria play a role in homeostasis of the circulatory system in mammals. First, gut bacteria may affect the nervous control of the circulatory system via the sensory fibres of the enteric nervous system. Second, gut bacteria-derived metabolites may cross the gut-blood barrier and target blood vessels, the heart and other organs involved in the regulation of the circulatory system. A number of studies have shown that hydrogen sulfide (H 2 S) is an important biological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 161 publications
2
102
0
2
Order By: Relevance
“…These levels appeared to be restored to the level found in the normal fecal samples when supplemented with each of the probiotic treatments ( Figure 4). The depletion of H 2 S observed in the C. difficile-infected fecal samples coincides with previous observations of inflammatory bowel conditions being associated with dysregulation of sulphate producing bacteria and disruption in some of the key functions of H 2 S such as colonic mucus production and maintenance of microbiota biofilm [79,80]. The ability of probiotic supplementation to increase and restore H 2 S levels in the C. difficile-infected fecal samples could be linked with the concurrent increased generation of acetate and butyrate.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These levels appeared to be restored to the level found in the normal fecal samples when supplemented with each of the probiotic treatments ( Figure 4). The depletion of H 2 S observed in the C. difficile-infected fecal samples coincides with previous observations of inflammatory bowel conditions being associated with dysregulation of sulphate producing bacteria and disruption in some of the key functions of H 2 S such as colonic mucus production and maintenance of microbiota biofilm [79,80]. The ability of probiotic supplementation to increase and restore H 2 S levels in the C. difficile-infected fecal samples could be linked with the concurrent increased generation of acetate and butyrate.…”
Section: Discussionsupporting
confidence: 88%
“…High levels of NH 4 have been linked to cytotoxic effects on the gut lumen, contributing to the formation of colorectal cancer [77,78]. Similarly, H 2 S has been linked to a range of toxicity pathways [79,80]. The results from the present work show that NH 4 production in the GI model was within the normal range of NH 4 production in the human gut lumen [36,39].…”
Section: Discussionsupporting
confidence: 56%
“…First, seafood rich in TMA and TMAO is widely thought to lower CVD risk (50). Second, as mentioned, an early study of TMAU patients found a high incidence of hypertension in the TMAUafflicted group (43).…”
Section: Atherosclerosis and Cardiovascular Disease (Cvd)mentioning
confidence: 97%
“…A very sophisticated control regulates its activity and contributes to maintaining a fine homeostasis. This regulation (similarly to that regulating the entire cardiovascular system) is dominated by the central nervous system (CNS) [151], the knowledge of which in the past 20 years has significantly evolved. This control is also supported, or rather induced by autonomic nervous system (ANS) [152], which completes the primary ring of homeostasis body's control along with the immune and endocrine systems.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%